A COMPARATIVE ANALYSIS OF TECHNOLOGICAL INTEGRATION IN DIAGNOSTIC PRACTICES ACROSS MEDICAL SPECIALTIES IN EXAMINING THE IMPACT ON X-RAY, LABORATORY, AND OPTOMETRY TECHNIQUES - Nasser Salem Ali Al Khuraym, Mahdi ZaidinZamyAlzbadeen, Saeed Saleh Muhammad Zabadin, Saleh Hassan Husain Alzabaden, Zidane Saleh Muhammad Zabadin, Mansour Saeed Althaibah, BadieDifallahQassim Al Mashham, Saleh Hamad Hassan Alyami (Chelonian Research Foundation, 2023)
Technological progress has revolutionized diagnostics over the therapeutic forte, progressing productivity, precision, and eventually Patient results. This article looks at the imperative part of innovation in determination, centring on x-ray specialists, pathologists, pathologist deals, and other doctors. Recognizing illustrations of effective collaborations highlights the changing nature of innovation in daily health and Patient care. Innovative progress empowers specialists to analyse conditions more rapidly and precisely, from advanced scanners that disentangle imaging methods for X-ray specialists to mechanized testing strategies that revolutionize the research facility. Optometrists utilize innovations such as coherence tomography (OCT) to affect eye disorders involving patients. Through collaboration between clinicians, innovation engineers, and arrangement creators, the integration of symptomatic innovation proceeds, giving openings that positively affect care and moving forward long-standing times of time.